2014
DOI: 10.1007/s11483-014-9358-z
|View full text |Cite
|
Sign up to set email alerts
|

Casein Micelles at Non-Ambient Pressure Studied by Neutron Scattering

Abstract: The disruption of casein micelles, as found in cows' milk, was investigated at pressures up to 300 MPa with small angle neutron scattering (SANS). From the decrease of the overall level of scattering, the expected disruption of the micelles was concluded. This disruption was incomplete, and stable at 300 MPa, independent of pressure history. At intermediate pressures, pressure history, (step-wise increase from ambient, or stepwise decrease from 300 MPa) had a strong effect on the scattering patterns. At high p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…The presence of individual CN molecules in milk serum is energetically unfavorable. Thus, these CN molecules can either assemble into new smaller micelles or adsorb at the surface of the remaining CN micelles, favoring the formation of a higher content of small micelles together with a fraction of large micelles (Knudsen & Skibsted, 2010; Ni et al., 2021; Olsen & Orlien, 2016; Tromp et al., 2015).…”
Section: Overview Of the Effects Of Hhp On Cn And Casein Micellesmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of individual CN molecules in milk serum is energetically unfavorable. Thus, these CN molecules can either assemble into new smaller micelles or adsorb at the surface of the remaining CN micelles, favoring the formation of a higher content of small micelles together with a fraction of large micelles (Knudsen & Skibsted, 2010; Ni et al., 2021; Olsen & Orlien, 2016; Tromp et al., 2015).…”
Section: Overview Of the Effects Of Hhp On Cn And Casein Micellesmentioning
confidence: 99%
“…Slow decompression (0.8−1.2 MPa/s) results in a higher content of soluble CNs of smaller size compared with fast decompression (62.5 and 87.5 MPa/s) (Baier, Purschke, et al., 2015; Bravo et al., 2013, 2012). In addition, the pressure release phase is associated with the reassociation of submicelles through the reformation of the HHP‐disrupted electrostatic and hydrophobic interactions (Kiełczewska et al., 2020; Singh & Huppertz, 2020; Tromp et al., 2015; Z. Yang et al., 2018).…”
Section: Factors Affecting the Cn Modification Under Hhpmentioning
confidence: 99%
“…showed that 10 kDa-permeable levels of Ca were not increased after HP treatment, in line with expectations based on the fact that mineral speciation equilibria in milk at atmospheric pressure cannot accommodate elevated levels of dissolved calcium and phosphate. Although it was later shown that solubilisation of MCP did occur at elevated pressure (Hubbard, Caswell, Lüdemann, & Arnold, 2002;Tromp, Huppertz, & Kohlbrecher, 2015) and was indeed the cause of disruption of micelles under pressure, such changes in mineral equilibria reversed on return to atmospheric pressure. Considering other aforementioned causes of casein micelle dissociation, also those acting on casein interactions, i.e., deamidation (Miwa et al, 2010), pH increase (Huppertz et al, 2008;Odagiri & Nickerson, 1965;Vaia et al, 2006), addition of urea (Aoki et al, 1986;Holt, 1998;McGann & Fox, 1974;Smiddy et al, 2006) and addition of surfactants (Lefebvre-Cases et al, 1998) all decrease turbidity and increase non-sedimentable casein and calcium in milk.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms leading to a given texture observed after treatment are not fully understood. In-situ techniques are useful to elucidate these mechanisms (Tromp, Huppertz, & Kohlbrecher, 2014;Gebhardt, Takeda, Kulozik, & Doster, 2011). Here, we introduce the use of ultrasonic measurements to address pressure-induced phenomena during high pressure processing of milk.…”
Section: Introductionmentioning
confidence: 99%